Proximal tibiofibular joint dislocation with Maisonneuve fracture and syndesmosis injury: A case report - Ganci, Marco; Panvini, Flora Maria Chiara; Kory, Antonio; Ortuso, Rocco; sicurella, Mirko; Prestianni, Ignazio; Cuffaro, Enrica Rosalia; Ferrara, Alessio; Longo, Gianfranco; Papotto, Giacomo (Acta Biomedica Atenei Parmensis, 2025)
Background: Proximal tibiofibular joint dislocation, a seldom-reported injury often overshadowed in polytrauma cases, remains underexplored. This study presents an unusual case featuring a postero-lateral variant of proximal tibiofibular joint dislocation with additional associated lesions.Case Presentation: A 66-year-old Italian male, post high-energy car collision, exhibited distinct common peroneal nerve palsy symptoms, revealing an atypical left Maisonneuve fracture with postero-lateral fibular dislocation and tibial mortise diastasis. Surgical intervention, post-stabilization, encompassed exploration and stabilization of the proximal tibiofibular joint and common peroneal nerve. Proximal joint stabilization with 2 cancellous screws and Maisonneuve fracture fixation with a plate followed, along with stabilization of tibial mortise diastasis using a plate and syndesmotic screws. Intra-operative fluoroscopy confirmed anatomical reduction, enabling partial progressive weight-bearing post-transyndesmotic screw removal.Conclusion: Surgical intervention yielded positive outcomes, including full weight-bearing, pain relief, and restored nerve function at the 12-month follow-up, emphasizing the necessity of a comprehensive surgical approach for optimal recovery